1990
DOI: 10.1073/pnas.87.10.3952
|View full text |Cite
|
Sign up to set email alerts
|

Topographical relationship between beta-amyloid and tau protein epitopes in tangle-bearing cells in Alzheimer disease.

Abstract: Double-labeling immunohistochemistry was used to investigate the topographical relationship between j3-amyloid and tau protein epitopes present in cells bearing neurofibrillary tangles found in the hippocampal formation of patients with Alzheimer disease. An antiserum raised against the amino terminus of fl-amyloid stained numerous tanglebearing cells and other bodies ("extracellular tangles"), but double labeling showed that the fi-amyloid staining is invariably peripheral to that of the tau-positive tangle p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
22
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Masters and collaborators published in 1985 that A␤, initially termed amyloid A4, is deposited first intraneuronally as NFT and subsequently in the extracellular space, associated with senile plaques and blood vessels [5]. Later on, the immunolabeling of most intraneuronal NFT (iNFT) and extraneuronal NFT (eNFT) with anti-A␤ antibodies was replicated in several laboratories [6][7][8] However, other studies failed to find A␤ immunolabeling associated with iNFT [9][10][11] or with both iNFT and eNFT [12].Later on, immunostaining with specific antibodies against the C-terminal fragment of either A␤ 40 or A␤ 42 (A␤ x-40 or A␤ x-42 , respectively) enabled the visualization of A␤ 42 associated with iNFT where it was seen to collocalize with tau, whereas A␤ 40 did not associate at all or to a far lesser degree [13][14][15]. Additionally, it was reported that numerous eNFT appeared stained for A␤ x-40 , which was interpreted as a secondary deposition over remnants of iNFT exposed in brain tissue once the cells died; however, evidence of colocalization of A␤ x-40 with tau protein in these eNFT was lacking [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Masters and collaborators published in 1985 that A␤, initially termed amyloid A4, is deposited first intraneuronally as NFT and subsequently in the extracellular space, associated with senile plaques and blood vessels [5]. Later on, the immunolabeling of most intraneuronal NFT (iNFT) and extraneuronal NFT (eNFT) with anti-A␤ antibodies was replicated in several laboratories [6][7][8] However, other studies failed to find A␤ immunolabeling associated with iNFT [9][10][11] or with both iNFT and eNFT [12].Later on, immunostaining with specific antibodies against the C-terminal fragment of either A␤ 40 or A␤ 42 (A␤ x-40 or A␤ x-42 , respectively) enabled the visualization of A␤ 42 associated with iNFT where it was seen to collocalize with tau, whereas A␤ 40 did not associate at all or to a far lesser degree [13][14][15]. Additionally, it was reported that numerous eNFT appeared stained for A␤ x-40 , which was interpreted as a secondary deposition over remnants of iNFT exposed in brain tissue once the cells died; however, evidence of colocalization of A␤ x-40 with tau protein in these eNFT was lacking [16].…”
mentioning
confidence: 99%
“…Masters and collaborators published in 1985 that A␤, initially termed amyloid A4, is deposited first intraneuronally as NFT and subsequently in the extracellular space, associated with senile plaques and blood vessels [5]. Later on, the immunolabeling of most intraneuronal NFT (iNFT) and extraneuronal NFT (eNFT) with anti-A␤ antibodies was replicated in several laboratories [6][7][8].…”
mentioning
confidence: 99%
“…Tissue sections from familial MSTD, AD, and control brains were incubated overnight at 4ЊC with the primary antibody and were processed for single and double staining as described (42). When the anti-A␤-antibody was used, tissue sections were preincubated for 5 min in 90% formic acid before incubation with the first antibody.…”
mentioning
confidence: 99%
“…§1734 solely to indicate this fact. and neuronal death (1,2,11,12). The specific details of this process are lacking, however, and whether neurons die by passive necrosis or by programmed cell death requiring protein synthesis is a matter of speculation.…”
mentioning
confidence: 99%
“…Rat tau protein expressed in Escherichia coli BL21 was purified as described (15). One microliter of cell extract was added to aliquots of a solution of recombinant rat tau (400 gg/ml) in buffer A containing 1 mM [y-t32P]ATP (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) Ci/mmol; 1 Ci = 37 GBq) and 10 ,uM okadaic acid, to a final volume of 10 ,ul. After incubation at 37°C for 3 hr, the reaction was stopped by adding SDS sample buffer.…”
mentioning
confidence: 99%